Tatkala Kampung Kota Bicara Konflik-Harmonisasi - - Pratiwi; Niken B. Pratiwi; Tiara Elgifienda (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2008)
Suburban becomes a marginal community as the result of government's construction and society based on government's developing program. These research explain the effect of disparity development. And it creates the victim, which is the rural city. The delayed of development become worse when the conflict is in the rural city. Collectivism and tolerance of interaction in rural city. and it lost when the individualism in the society. Godeireng's citizen as known as beggar, and vagrant and it bring the negative perspective. The conflict caused disintegration. By the time and the effort of youth, the citizen propose the development program for all. It is the start of harmonization process to build a better rural.